Լազերային լիպոսակցիայի կլինիկական մի շարք ասպեկտներ - Վ. Գ. Մկրտչյան (Հայաստանի ԳԱԱ)
Представлены клинические результаты лазерной липосакции 193 пациентов разных полов в возрасте 30-61 год , страдающих от ожирения с различной локализацией жира. Полученные данные свидетельствуют, что использование лазерной липосакции является основополагающим и важным, значительно улучшает качество жизни пациентов, позволяет вернуться к повседневной деятельности.The article presents the clinical results of laser liposuction of 193 patients of both sexes at the ages of 30-61 years suffering from obesity with different localization of fat. The findings suggest that the use of laser liposuction is fundamental and important, it significantly improves the quality of life of patients, allowing them to return to the daily life activities.
Keywords: Medicine; Surgery